The Czech Republic's banking sector: Emerging from turbulent times - Dana Hájková; Jan Hanousek; Libor Němeček (EIB Papers, 2002)
In contrast to many other accession countries of Central and Eastern Europe (CEECs), the Czech Republic experienced a shorter and less severe transition recession in the first half of the 1990s. The decline in output lasted two years and by 1995, real GDP had returned to its 1989 level. Unemployment was surprisingly low, averaging less than 3 percent in 1990-95. In addition, stabilisation policies (the fixing and devaluation of the exchange rate, tight fiscal and monetary policies, and initial wage discipline) led to a fast reduction in inflation to single-digit levels and, thus, to internal as well as external stability. The liberalisation of prices, wages and trade, along with the fast launching of mass privatisation of state property were seen as major achievements in getting the country on a path to prosperity. A number of observers have noted that what appeared like a smooth transition from socialism to capitalism was in fact a sign that a fundamental reorientation of the Czech economy was yet to come. We agree with this assessment. What is more, one of our main hypothesis is that the country's apparent success at output and macroeconomic stabilisation in the early phase of transition distracted from addressing fundamental problems of the banking sector and corporate governance. That these problems were real became evident with the massive accumulation of nonperforming loans on banks' balance sheets, bank failures, and the economic recession in the second half of the 1990s.
Keywords: 330; Bank; Reorganisation; Eigentümerstruktur; Bankenkrise; EU-Erweiterung; Tschechische Republik